A Proposal for CRMS Indonesia to enhance the Market Share in Indonesia - Salim, Lea Shaula; Paramarta, Riawan B (The Indonesian Journal of Business Administration, 2015)
Abstract - The needs of risk management in Indonesia is increasing since there are a regulation from the Indonesian government to implement risk management Badan Usaha Milik Negara (BUMN), Listed Companies, Banking and Non Banking sectors. To fulfill this needs, CRMS Indonesia as an  risk management training firms has several programs and  product to be offered to the market with ISO 31000 standard.  Even the needs of risk management is big, the market share of CRMS Indonesia is 11.8% in 2014. And the other 88.2% of market potential is still outside. Market share become concern because it shows CRMS Indonesia domination in market. The revenue will automatically increase when the market share increase. Risk management training firms commonly do the same process and marketing mix. The analysis shown that position of CRMS Indonesia compare with the existing competitor is strong enough, because they have two programs that could become the competitive advantage such as international benchmarking and  roundtable disscussion. But the weaker position face by this training firms, because the number of bargaining power of supplier is stronger in here. Furthermore, online learning is one of threats for substitute product.  CRMS Indonesia itself, has a strength in networking with international institutions, experienced faciliator, and recognition as the Risk Management Service Provider of The Year in 2014 from Institution of Risk Management in London. All of those strength can be used to increase the market share. But the root cause found are they lack  number of faciliator, lack number of team and the delivery method need improvement. Those indicates the reason why the market share of CRMS Indonesia is not maximum. The solution for the root cause are the planning for the partnership solution, recruitment solution, customer relationship management solution, and e-learning solution. Those solution are expected to help CRMS Indonesia in enhancing the market share in Indonesia. Keywords : Risk Management, Training Firms, Indonesian Regulations